2021
DOI: 10.3389/fcell.2021.694276
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pancreatic Stellate Cells Is Beneficial for Exocrine but Not Endocrine Cell Differentiation in the Developing Human Pancreas

Abstract: Pancreatic stellate cells (PaSCs) are non-endocrine, mesenchymal-like cells that reside within the peri-pancreatic tissue of the rodent and human pancreas. PaSCs regulate extracellular matrix (ECM) turnover in maintaining the integrity of pancreatic tissue architecture. Although there is evidence indicating that PaSCs are involved in islet cell survival and function, its role in islet cell differentiation during human pancreatic development remains unclear. The present study examines the expression pattern and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
(122 reference statements)
0
13
0
Order By: Relevance
“…Additionally, reversing activated PSCs back to a quiescent state might also sensitize pancreatic cancer ferroptosis. It has been indicated that ATRA could keep PSCs in a quiescent state and reduce pancreatic fibrosis [ 25 ]. Combining ATRA with ferroptosis inducers may be able to mitigate the effects of the dense microenvironment of pancreatic cancer on treatment resistance [ 26 ] and provide a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, reversing activated PSCs back to a quiescent state might also sensitize pancreatic cancer ferroptosis. It has been indicated that ATRA could keep PSCs in a quiescent state and reduce pancreatic fibrosis [ 25 ]. Combining ATRA with ferroptosis inducers may be able to mitigate the effects of the dense microenvironment of pancreatic cancer on treatment resistance [ 26 ] and provide a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant N-acetylcysteine (NAC) attenuates this effect, suggesting that hypoxic PSCs increase oxidative stress ( Kim et al, 2020 ). The presence of activated PSCs also inhibits differentiation of fetal islet–epithelial cell clusters into insulin-positive cells, indicating suppressive effects on islet cells ( Li et al, 2021b ). High glucose conditions, derived from DM, activate PSCs by elevating oxidative stress ( Ryu et al, 2013 ).…”
Section: Effects Of Metabolic Changes In Pscs and Normal Pancreatic C...mentioning
confidence: 99%
“…Pancreatic stellate cells secrete extracellular matrix proteins and seem to have a significant function in the first trimester of human pancreatic development by enhancing differentiation to exocrine cell lineages ( 14 ).…”
Section: Intrauterine Pancreas Developmentmentioning
confidence: 99%